1960
DOI: 10.1080/00288233.1960.10419866
|View full text |Cite
|
Sign up to set email alerts
|

The effects of frequent hard grazings at different times of the year on the productivity and species yields of a grass-clover pasture

Abstract: An experiment is described in which the effects of frequent hard grazings at different times of the ye'ar on the productivity and species yields of a pasture of short-rotation ryegrass, cocksfoot, and red and white clover were determined over an eighteen-month period. Frequent hard grazings during the winter encouraged the growth of all sown species, and dry-matter (d.m.) yields were high for these pastures after a change to less-intensive grazing in later seasons. Frequent hard grazings during the spring redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
0
13

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(78 citation statements)
references
References 2 publications
8
54
0
13
Order By: Relevance
“…Both chicory and red clover responded negatively to frequent grazing with particularly large responses for red clover. Responses for red clover are similar to those reported at the same site by Brougham (1959Brougham ( , 1960, particularly under hard grazing (low pasture residual after grazing) e.g., 74% yield reduction, and by Cosgrove & Brougham (1985) who reported that grazing frequency had the greatest influence in summer (50% yield reduction) with a 38% reduction in annual production. Comparatively lower responses for chicory are in line with results from this site in two short-term cutting experiments on pure chicory stands during late spring/early summer and late summer/autumn.…”
Section: Grazing Frequencysupporting
confidence: 73%
“…Both chicory and red clover responded negatively to frequent grazing with particularly large responses for red clover. Responses for red clover are similar to those reported at the same site by Brougham (1959Brougham ( , 1960, particularly under hard grazing (low pasture residual after grazing) e.g., 74% yield reduction, and by Cosgrove & Brougham (1985) who reported that grazing frequency had the greatest influence in summer (50% yield reduction) with a 38% reduction in annual production. Comparatively lower responses for chicory are in line with results from this site in two short-term cutting experiments on pure chicory stands during late spring/early summer and late summer/autumn.…”
Section: Grazing Frequencysupporting
confidence: 73%
“…This leaf elongation rate increase for intense and variable post-grazing height can result in higher forage production, once this morphogenetic characteristic particularly most relates to forage yield (Horst et al, 1978) and tiller emergence (Nelson et al, 1977). The present results are supported by the results of Brougham (1959Brougham ( , 1960, whose management procedures adopted in one season affected the forage yield in the subsequent ones. However, further research with Panicum maximum is needed to corroborate these patterns.…”
Section: Discussionsupporting
confidence: 79%
“…For instance, a change in grazing seasonality leads to different vegetation productivity levels, species, and structures (Marble and Harper, 1989;Mousel et al, 2003;Metzger et al, 2005). Brougham (1960) showed that frequent hard summer grazing activities resulted in the widespread death of desirable pasture plants in New Zealand. Ludwig (2000) has discussed that the activities of livestock were concentrated in the places near water owing to the animals' physiological dependence.…”
mentioning
confidence: 99%